Interpretation of the Tube Coagulase Test for Identification of Staphylococcus aureus - Sperber, W.H. (1975)
The tube coagulase test is a valid means of identifying Staphylococcus aureus, provided that only a firm clot that does not move when the tube is tipped is considered a positive reaction. The widely promulgated interpretation that all degrees of clotting in coagulase plasma are a positive identification of S. aureus was disproved by the use of other tests such as anaerobic glucose fermentation thermonuclease production, and lysostaphin sensitivity. It was found that the source of supply of the coagulase plasma is a factor in the occurrence of false-positive coagulase test results. The use of pig and rabbit plasma in the tube coagulase test is also discussed.